Growth Factor Concentrations in Human Milk Are Associated With Infant Weight and BMI From Birth to 5 Years - Laura Galante; Shikha Pundir; Hanna Lagström; Samuli Rautava; Clare Marie Reynolds; Amber Marie Milan; David Cameron-Smith; Mark Hedley Vickers (FRONTIERS MEDIA SA, 2022)
Background:Human milk bioactives may play a role in infant health and development. Although the variability in their concentrations in milk is well-established, the impact of differential milk profiles on infant growth outcomes remains unclear. Thus, the aim of the present study was to investigate whether different concentrations of metabolic hormones are associated with different weight and BMI in infants beyond the first year of life. Methods:Milk samples at 2.6 (+/- 0.4) months after birth and anthropometric measures at 13 months, 2, 3, and 5 years were collected as part of the Finnish STEPS cohort study from 501 mothers and the respective 507 infants. Leptin, adiponectin, insulin-like growth factor (IGF)-1 and cyclic glycine-proline (cGP) in milk were analyzed. Multiple regression models and a repeated measures mixed model were used to examine associations between milk hormone concentrations and weight and BMI z-scores across time, at each time-point, and weight gain from birth to each follow-up visit. All models were corrected for birth weight, infant sex, duration of exclusive and total breastfeeding, time of introduction of solid foods and maternal pre-pregnancy BMI. Results:Higher milk IGF-1 was associated with higher weight at 13 months (p= 0.004) but lower weight at 3 (p= 0.011) and 5 years of age (p= 0.049). Higher cGP was associated with lower weight across the 5 years (p= 0.019) but with higher BMI at 5 years (p= 0.021). Leptin and adiponectin did not display associations with infant growth at this time. Sex interactions were also absent. Conclusions:Our results suggest that the interplay between human milk-borne IGF-1 and cGP is similar to that reported in other mammals and may have an important role in defining infant growth trajectories beyond the first year of life. Further research should explore the determinants and origins of these milk-borne compounds and evaluate their effect on infant growth and metabolism.